Using MEST-C Scores and the International Study of Kidney Disease in Children Classification to Predict Outcomes of Henoch–Schönlein Purpura Nephritis in Children - Wang, Meiqiu; Wang, Ren; He, Xu; Zhang, Pei; Kuang, Qianhuining; Yao, Jun; Fang, Xiang; Shi, Zhuo; Wu, Heyan; Peng, Yingchao; Xia, Zhengkun; Gao, Chunlin (Frontiers in Pediatrics, 2021)
Abstract Introduction Henoch-Schönlein purpura nephritis (HSPN) and IgA nephropathy (IgAN) bear similarity in some aspects. The histological classification of HSPN was built on the International Study of Kidney Disease in Children (ISKDC) criteria, while IgAN was established on the 2016 Oxford Classification (MEST-C scores). The purpose of this paper was to discuss the predictive value of ISKDC classification and MEST-C scores in children with HSPN. Methods We analyzed retrospective statistical evidence from 877 children with HSPN included in a single-center between 2001 and 2019. The primary outcome was defined as chronic kidney disease —— estimated glomerular filtration rate(eGFR) < 90 mL/min/1.73m2. Results During the follow-up period of 23.3(10.9-47.9) months, 51(5.8%) patients reached the primary outcome. As is revealed in a Kaplan–Meier plot, segmental glomerulosclerosis(S) (P<0.001) and tubular atrophy/interstitial fibrosis(T) (P<0.001) significantly predict the poor renal outcome. Other Oxford lesions and ISKDC classification, however, did not show a significant difference in a worse outcome. In a multivariate Cox model adjusted for pathological and clinical factors, eGFR (HR=2.831, 95%CI=1.359-5.896), S lesion (HR=3.936, 95%CI=2.078-7.457) and T lesion (HR=4.002, 95%CI=1.733-9.242) were independent risk factors for renal outcome. Conclusion This series constitutes the largest series reported so far in the literature of such patients. According to our findings, S and T of Oxford classification, which is ignored by the ISKDC classification, could be applied to predict the renal prognosis of children with HSPN. Keywords Henoch–Schönlein purpura nephritis, Oxford classification, MEST-C scores, Immunoglobulin A vasculitis, International study of kidney disease in children classification